2013
DOI: 10.1371/journal.pone.0081271
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms Produce phytochelatins in Response to Arsenic

Abstract: Phytochelatins are small cysteine-rich non-ribosomal peptides that chelate soft metal and metalloid ions, such as cadmium and arsenic. They are widely produced by plants and microbes; phytochelatin synthase genes are also present in animal species from several different phyla, but there is still little known about whether these genes are functional in animals, and if so, whether they are metal-responsive. We analysed phytochelatin production by direct chemical analysis in Lumbricus rubellus earthworms exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 48 publications
(60 reference statements)
1
33
0
Order By: Relevance
“…Studies on metal pollution which have not analysed PCs may turn out to give an incomplete picture . Indeed, recent studies have shown direct responses of PCs to metal(loid) ions in animal species from additional phyla, including earthworms (Annelida) and sea squirts (Chordata) (Franchi et al, 2014;Liebeke et al, 2013). This, again, highlights the potential significance of PCs in the context of environmental pollution research, as they are found in phyla with members from the terrestrial, freshwater, and marine environments.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies on metal pollution which have not analysed PCs may turn out to give an incomplete picture . Indeed, recent studies have shown direct responses of PCs to metal(loid) ions in animal species from additional phyla, including earthworms (Annelida) and sea squirts (Chordata) (Franchi et al, 2014;Liebeke et al, 2013). This, again, highlights the potential significance of PCs in the context of environmental pollution research, as they are found in phyla with members from the terrestrial, freshwater, and marine environments.…”
Section: Introductionmentioning
confidence: 89%
“…Following centrifugation (5 min, 16,000 g), the supernatants were derivatized with 60 μl of 266 mM N-ethyl maleimide. We then analysed the phytochelatins PC 2 and PC 3 using a targetted LC-MS-MS method, based on the approach of Liebeke et al (2013). Briefly, samples were injected onto an Agilent 1200 HPLC system coupled to a SCIEX 6500 Q-TRAP mass spectrometer (AB SCIEX, Warrington, UK) operated in High Mass negative mode.…”
Section: Pc Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These are: (i) a homologous of ␥-glutamyl transpeptidase, the enzyme responsible for the exogenous degradation of glutathione (Table S1), suggesting that these parasites have the ability to catch and metabolize exogenous glutathione [51]; (ii) the enzyme phytochelatin synthase (Table S2), which is involved in the generation of the glutathione-derived biopolymers named phytochelatins [52]. Although the importance of this enzyme is unknown [53], it has been proposed that could be involved in metal detoxification that can generate ROS [54], as well as in elimination of compounds generated with glutathione S-transferase [55]. In this sense, in preliminary HPLC experiments, we have found the presence of three low molecular weight thiol-containing peptides (Fig.…”
Section: Glutathione Metabolism In Platyhelminthsmentioning
confidence: 99%
“…A recent study has now given us a third data point: the earthworm Lumbricus rubellus (phylum Annelida) produced phytochelatins in response to arsenic, both in laboratory exposures ( Figure 1) and in worms sampled from contaminated field sites. 5 Admittedly, this means we still only have data from three phyla, but it does demonstrate that phytochelatin responsiveness to PTEs is not unique to nematodes.…”
mentioning
confidence: 99%